Pasteurella multocida toxin manipulates T cell differentiation - Hildebrand, Dagmar; Heeg, Klaus; Kubatzky, Katharina F. (Frontiers in Microbiology, 2015)
Pasteurella multocida causes various diseases in a broad range of wild and domestic animals. Toxigenic strains of the serotypes A and D produce an AB protein toxin named Pasteurella multocida Toxin (PMT). PMT constitutively activates the heterotrimeric G protein subunits Gαq, Gα13 and Gαi through deamidation of a glutamine residue, which results in cytoskeletal rearrangements, increased proliferation and survival of the host cell. In human monocytes, PMT alters the lipopolysaccharide (LPS)-induced activation towards a phenotype that suppresses T cell activation. Here we describe that the toxin also modulates CD4-positive T helper (Th) cells directly. PMT amplifies the expansion of Th cells through enhanced cell cycle progression and suppression of apoptosis and manipulates the differentiation of Th subclasses through activation of Signal Transducers and Activators of Transcription (STAT) family members and induction of subtype-specific master transcription factors. A large population of toxin-treated T cells is double-positive for RORγt and Foxp3, the transcription factors expressed by Treg and Th17 cells, respectively. This suggests that these cells could have the potential to turn into Th17 cells or suppressive Treg cells. However, in terms of function the PMT-differentiated cells behave as inflammatory Th17 cells that produce IL-17 and trigger T cell proliferation.